Inovasi Proses Pelayanan Dokumen Kependudukan Terintegrasi di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sumenep - Novi Nur Ariska; Selfi Budi Helpiastuti; Agus Suharsono (Electronical Journal of Social and Political Sciences (E-SOSPOL), 2023)
This study aims to analyze the process innovation of integrated population documents at the Department of Population and Civil Registration of Sumenep Regency. The Department of Population and Civil Registration (Disdukcapil) of Sumenep Regency, as the implementing element of population administration services, still faces several problems due to the lengthy process of providing services. Therefore, Disdukcapil made an improvement by launching an integrated population document service innovation. This innovation brings new work processes or service procedures to make it easier and faster. This study aims to describe the innovation of integrated population document services at Disdukcapil, Sumenep Regency. The type of research used is the paradigm post-positivism with a qualitative approach. The data analysis used is interactive model data analysis. The results of this study indicate that the process innovation in the integrated population document service launched by the Sumenep Regency Disdukcapil is still not fully optimal, but there has been a renewal in the process innovation launched, as seen from the simplification of the service process offline and also the availability of servicesonline. It’s just that, in its implementation it still encounters several obstacles, including the service process in person online provided is still not able to be used properly by the island community because access to the internet network is still difficult to reach. In addition, there were complaints regarding the attitude of employees who were still considered unfriendly and lacking in discipline which contributed to suboptimal community satisfaction.